Graphene/PDMS composite microstructure for pressure sensor application by 3D printing. Issue 6 (April 2019) - Liu, Yang; Shi, Jianhao; Yang, Zhuoqing; Wang, Xuhong; Guo, Zhichao; Ding, Guifu
Abstract: In this paper, for the first time, we develop a method to fabricate and pattern graphene/PDMS (polydimethylsiloxane) composite film based on PDMS microchannels and graphene microfluids for pressure sensor application. The resistance response of the pressure sensor can be adjusted by changing graphene proportion of graphene/PDMS composite film. In addition, good stability has been demonstrated according to the repeatability test result. Fast response (88 ms) has also been tested, which shows good potential in flexible tactile sensing application.